Design of a Web-Based Geographic Information System for Mapping Coastal Areas and Fishermen's Activities on Bintan Island - Fortia Magfira; Indah Kartika; Marisha Pertiwi; Nida Mardhiyah Ramdhani (Politeknik Negeri Batam, 2025)
Coastal ecosystems and small-scale fisheries in Pengudang Village, Bintan, play an essential role in supporting local livelihoods. However, integrated spatial information on benthic habitats, mangroves, and fishing activities remains limited. This study aims to map coastal ecological conditions and fishing grounds while developing an accessible Web-GIS system to support coastal management. A descriptive qualitative approach was employed. Sentinel-2 Level 2A imagery was analyzed using Maximum Likelihood Classification, supported by field surveys, ground truthing, and interviews with 20 active fishers. Mangrove density was assessed using NDVI analysis. Spatial data, combined with fishers’ activity information, were integrated into a Web-GIS developed using the SDLC Waterfall method. The classification generated four dominant benthic habitat classes including seagrass, sand, mixed substrate, and dead coral with algae. NDVI indicated varying mangrove density levels from low to very high. Fishing grounds were concentrated in shallow waters with seagrass and mixed substrates. Fishers predominantly used kelong and bubu, producing 5–20 kg catch per trip. The developed Web-GIS provides interactive maps, layer selection, and spatial search features. The system enhances accessibility to coastal spatial data and supports evidence-based decision-making for sustainable coastal resource management in Pengudang Village.